The effect of oral healthcare education on caregivers of physically and mentally disabled individuals - Maryam Sadeghipour; Mohammad Hossein Khoshnevisan; Mahshid Namdari; Mahsa Malek-Mohammadi; Reza Golpayegani (Journal of Oral Health and Oral Epidemiology, 2022)
Background: Special physical and mental conditions of disabled individuals are burdens to their utilization of proper oral healthcare. Their caregivers can be influential in improving their oral health status. This study sought to assess the effect of oral healthcare education on the knowledge, attitude, and practice of caregivers of physically and mentally disabled individuals.Methods: This quasi-experimental study evaluated 68 caregivers of physically and mentally disabled individuals selected from disability rehabilitation centers in Tehran by convenience sampling. A validated questionnaire was designed for data collection, including questions on demographics, knowledge, attitude, and practice of caregivers. A brochure was also designed to cover the content of the educational intervention, and the relevant topics were taught to caregivers using the face-to-face method. A pretest-posttest method was used for effectiveness assessment. All the caregivers filled out the questionnaire before and 3 months after the educational interventions. The pretest and posttest scores were compared using the Wilcoxon test and paired t test.Results: Sixty-three caregivers participated in this study, 80% of whom were women and 94% had more than one year of work experience. The results showed that the mean score of their knowledge (from 1.2 ± 0.82 to 4.82 ± 0.35), attitude (from 2.38 ± 0.69 to 5.61 ± 0.75), and practice (from 0.59 ± 0.41 to 4.93 ± 0.65) increased significantly after the intervention, which indicates the effectiveness of the intervention (P < 0.001).Conclusion: Educational intervention can significantly enhance the knowledge, attitude, and practice of caregivers of physically and mentally disabled individuals. This can, in turn, help improve the oral health status of the disabled individuals under their care.